A Classroom-Based Physical Activity Intervention for Elementary Student On-Task Behavior. Issue 3 (3rd July 2018) - Maykel, Cheryl; Bray, Melissa; Rogers, H. Jane
ABSTRACT: Few youths engage in the recommended amount of physical activity (PA). Many educators have concerns about increasing PA in schools, including taking time from academics, though studies show that school-based PA can be beneficial to academics. This study extends previous research on the relationship between school-based PA and time on task (TOT) by engaging students in teacher-led PA breaks in the classroom and observing students' on-task behavior for a longer period than previous studies. A third-grade class of 23 students from a rural New England public school was observed as part of a single-subject withdrawal design study. The class, therefore, served as its own control. Student on-task behavior was observed for 45 min following both inactive and active conditions using systematic direct observation procedures. The intervention consisted of 10 min of whole-body movement: 1–2 min of warm-ups, 6–8 min of moderate PA, and 1–2 min of cool-downs. Multiple measures of effect indicate that simple, 10-min, breaks for PA can improve TOT rates among elementary students. This study supports the use of brief breaks for PA to improve student TOT while also indicating that the effects persist for at least 45 min. This is valuable to educators who wish to increase TOT with a simple classroom intervention and for those who wish to help students meet the recommended amount of daily PA.